Research handbook on cross-border enforcement of intellectual property - Torremans, Paul (Northampton, MA : Edward Elgar, 2014)
The Research Handbook on Cross-border Enforcement of Intellectual Property systematically analyses the unique difficulties posed by cross-border intellectual property disputes in the modern world. The contributions to this book focus on the enforcement of intellectual property primarily from a cross-border perspective. Infringement remains a problematic issue for emerging economies and so the book assesses some of the enforcement structures in a selection of these countries, as well as cross-border enforcement from a private international law perspective. Finally, the book offers a unique insight into the roles played by judges and arbitrators involved in cross-border intellectual property dispute resolution. Providing a comprehensive approach to cross-border enforcement, this Handbook will prove a valuable resource for academics, postgraduate students, practitioners and international policymakers.
Pt. I. National and regional assessments -- pt. II. A private international law perspective -- pt. III. Judges and arbitrators -- pt. IV. Special issues.
Includes bibliographical references and index.
Keywords: Intellectual property; Conflict of laws -- Intellectual property